Medical-Legal Partnerships: a promising approach for addressing health-harming legal needs among people with HIV - Jaén, Julia; Frankel, Anne; French, Ashley; Davison, Robin; Munoz-Laboy, Miguel; Martinez, Omar (Frontiers in Sociology, 2024)
IntroductionPeople with HIV (PWH), particularly those at the intersection of sexual and gender identities, face enduring obstacles to accessing HIV care, including structural stigma, structural racism and discrimination, housing instability, and limited access to health insurance. To address these challenges, Medical-Legal Partnerships (MLPs) in HIV care offer an innovative approach that integrates medical and legal services. By targeting health-harming legal needs (HHLN), MLPs aim to enhance the HIV care continuum outcomes for PWH.MethodsThis study examines the benefits and challenges of MLPs within organizations serving PWH through the social-ecological model. MLP providers (n=111) identified organizational-level challenges such as funding limitations, resource integration issues, and staffing constraints.ResultsMLPs demonstrated numerous benefits, including patient impact and benefits, comprehensive service provision, enhanced staff support and capacity, and potential for policy influence.DiscussionThese results underscore the feasibility of MLPs while offering valuable insights into their efficacy and challenges, guiding the implementation of MLPs to address health-harming legal needs, including discrimination, and thereby improving HIV care outcomes.